Analisis Penunjukan Makna dalam Ushul Fiqh: Telaah atas Lafaz Amm dan Khash Beserta Aplikasi Nash dan Implikasi Hukumnya - Hardani H; Fatmawati F; Abd. Rauf Muhammad Amin (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the concepts of ‘Amm and Khâsh in uṣūl al-fiqh, which play a significant role in understanding the Qur’an and Hadith. The purpose of this research is to explain the meaning, types, and legal implications of general and specific expressions in Islamic legal interpretation. The method applied is library research by reviewing classical and contemporary scholarly works that discuss ‘Amm and Khâsh. The findings show that ‘Amm refers to expressions that apply to all individuals within a category without exception, while Khâsh points to a singular expression with a definite and limited meaning. This study also highlights three main forms of ‘Amm: ‘Amm yurâdu bihi ‘Amm, ‘Amm yurâdu bihi Khusûs, and ‘Amm makhsûs, whose interpretation depends heavily on context and qarīnah. In conclusion, a deeper understanding of ‘Amm and Khâsh is essential for ensuring accuracy in deriving Islamic laws and for affirming both the universal and specific nature of the Sharī‘ah in various situations